Text message reminders for vaccination of adolescents with chronic medical conditions: A randomized clinical trial. Issue 35 (16th August 2017) - Hofstetter, Annika M.; Barrett, Angela; Camargo, Stewin; Rosenthal, Susan L.; Stockwell, Melissa S.
Highlights: Text message reminders increase vaccination of adolescents with chronic conditions. Plain reminders are more effective than educational reminders in the short-term. Vaccine beliefs and practices differ between primary and subspecialty care providers. Novel strategies to increase receipt of specially-indicated vaccines are needed. Abstract: Background: Many adolescents with chronic medical conditions (CMCs) are at risk of vaccine-preventable infection, yet are frequently under-vaccinated. Text message reminders, particularly those with embedded educational information, have been shown to increase general pediatric vaccination. Their use has not been studied specifically among adolescents with CMCs. Methods: Eligible parents of adolescents with CMCs receiving care at one of 4 academically-affiliated pediatric clinics and requiring human papillomavirus (first dose), influenza, and/or pneumococcal polysaccharide vaccines were randomized in 4 consecutive cohorts to receive text message vaccine reminders with or without embedded educational information ("educational" vs . "plain" arm, respectively). Educational reminders, including one interactive message, addressed infection risk, vaccine safety/efficacy, and physician recommendations. Up to 5 weekly and 2 booster reminders were sent (October 2014–January 2015). Receipt of any needed vaccine and missed vaccination opportunities by 4, 12, and 24 weeks after the initial reminder were compared between arms. Results: Of randomized parents (n = 295), 175 (59.3%) were Spanish-speaking; most had adolescents with CMCs who were 13–17 years (n = 229; 77.6%) and publically insured (n = 272; 92.5%). Baseline demographics and parental vaccine beliefs were similar between arms. More adolescents in the plain vs. educational reminder arm received any needed vaccine by 4 weeks (31.9% vs . 22.7%, adjusted relative risk [aRR] 1.47, 95% CI 1.01–2.14), but not by 12 or 24 weeks. Plain reminders were noted in post hoc analyses to have a greater effect than educational reminders in certain sub-populations, including 11–12 year-olds and those sent the initial reminder in early fall. Fewer adolescents in the plain vs. educational reminder arm had a missed vaccination opportunity by 4 weeks (10.9% vs. 41.3%; aRR 0.21, 95% CI 0.07–0.60), but not by 12 or 24 weeks. Conclusion: Plain text message vaccine reminders appear to have a positive effect compared to educational ones in the short-term and for certain families. Trial registration:NCT02231957 (www.clinicaltrials.gov)